Skeletal muscle HSF1 prevents insulin resistance by improving glucose utilization. Issue 12 (24th November 2022) - Li, Yun; Lin, Shibo; Xu, Xu; Jin, Weilai; Su, Yinglin; Yuan, Fuqiang; Zhang, Yiting; Li, Zhengying; Zhou, Yahui; Zhu, Lihong; Zhang, Le
Abstract: The regulation of muscle glucose utilization has significant potential for the treatment of type 2 diabetes mellitus (T2DM) and obesity. Heat shock factor 1 (HSF1) is involved in cellular metabolism and regulation of muscle metabolism. However, it is unclear how HSF1 regulates muscle glucose metabolism. In the present study, the development of obesity in mice was associated with HSF1 downregulation. Serum samples and muscle biopsies were obtained from obese and healthy humans. Fasting glucose and insulin levels and the homeostasis model assessment of insulin resistance value showed that obesity was associated with insulin resistance. The skeletal muscle level of HSF1 was decreased in obese and ob/ob mice. HSF1 was selectively over‐expressed in the skeletal muscles of high fat diet (HFD)‐fed mice. Muscle HSF1 over‐expression successfully triggered glycolytic‐to‐oxidative myofiber switch and increased fatty acid metabolism and insulin sensitivity in the skeletal muscles of HFD‐fed mice. Moreover, HSF1 improved energy expenditure and blocked muscle accumulation of triglycerides in HFD‐fed mice. Consequently, muscle HSF1 mitigated the impaired muscle insulin signaling and insulin resistance in HFD‐fed mice. In conclusion, T2DM and obesity in HFD‐fed mice may be treated with selective HSF1‐directed programming of exercise‐like effects in skeletal muscle. These findings may aid the development of a new therapeutic approach for obesity and T2DM.